2014
DOI: 10.1007/s10142-014-0414-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic signal transduction and phosphate metabolism as adaptive strategies during citrus canker induction by Xanthomonas citri

Abstract: The genome of Xanthomonas citri subsp. Citri strain 306 pathotype A (Xac) was completely sequenced more than 10 years; to date, few studies involving functional genomics Xac and its host compatible have been developed, specially related to adaptive events that allow the survival of Xac within the plant. Proteomic analysis of Xac showed that the processes of chemotactic signal transduction and phosphate metabolism are key adaptive strategies during the interaction of a pathogenic bacterium with its plant host. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 48 publications
1
32
0
1
Order By: Relevance
“…MCPs sense beneficial or toxic environmental compounds and transduce the signal to the cytoplasm by CheW protein, causing changes in the flagella direction and rotation speed, which finally guides bacterial cells to favorable environments [54,55]. Here, we have found that the core repertoire of the MCPs in nine genome sequences of X .…”
Section: Discussionmentioning
confidence: 98%
“…MCPs sense beneficial or toxic environmental compounds and transduce the signal to the cytoplasm by CheW protein, causing changes in the flagella direction and rotation speed, which finally guides bacterial cells to favorable environments [54,55]. Here, we have found that the core repertoire of the MCPs in nine genome sequences of X .…”
Section: Discussionmentioning
confidence: 98%
“…4. Some extensively modified proteins included regulators such as PhoR, which regulates PhoBPA to sense phosphate and iron [10]; VicR, which senses osmotic stress [11]; PilR, which is a transcriptional regulator for pilin and other genes required for Fe (III) reduction [12]; and methyl-accepting chemotaxis protein (MCP) and CheW, which are involved in chemotaxis [13]. The F-type ATPase was also found to have unique PTMs.…”
Section: Resultsmentioning
confidence: 99%
“…Two proteins exhibited confidence scores higher than 0.5 for this interaction: FliL and FliM. FliL is a flagellar protein part of flagellar regulon and required for flagellar function (Wolfe and Visick, 2008;Moreira et al, 2015), whereas FliM is a flagellar motor switch protein, one of three proteins (FliG, FliN, FliM) that forms the rotor-mounted switch complex (C ring), located at the base of the basal body (Moreira et al, 2015).…”
Section: Discussionmentioning
confidence: 99%